THE INCREASING PREVALENCE OF ACUTE RESPIRATORY INFECTIONS AMONG INFANTS AND CHILDREN AND SUGGESTED NUTRITIONAL PREVENTION AND PRESCRIPTION: A LITERATURE REVIEW - Lukmana, Arya Ananda Indrajaya; Pelangi, Bunga; Kusuma, Refani Alycia; Wulandari, Alifah (Journal of Indonesian Specialized Nutrition, 2026)
Background: Acute respiratory infections (ARI) are a significant cause of illness and death in infants and children under five. Infants' nutritional status and feeding patterns are factors that affect their vulnerability to ARI. This literature review aimed to summarize the incidence of ARI, the risk factors, and the evaluation of nutritional strategies. Methods: The literature review was conducted using articles published between January 2020 and December 2025. A search was conducted in PubMed and Scopus using keywords related to ARI. Results: ARI is very common among children under 5 years old. Malnutrition and low birth weight correlate with heightened risk and severity of ARI. Insufficient exclusive breastfeeding practices are associated with an increased risk of ARI, while exclusive breastfeeding has a protective effect. Environmental factors affect the likelihood of ARI. Evidence on micronutrient supplementation is varied and not ideal. Conclusion: Interventions for ARI in children require an integrated strategy that focuses on exclusive breastfeeding, improved nutritional status, and a healthier household environment.